The Oppression of Women in the Fairy Tale Frau Holle: A Feminist Literary Critique - Nisa Utami, Alvidya; Ahmadi, Anas (Jurnal Hata Poda, 2025)
The Feminism is a belief that men and women should have equal rights in politics, society, sexuality, intellect, and economics. Feminism encompasses movements, theories, philosophies, and everything related to gender equality with the goal of achieving justice for women.Women's Oppression has been a theme in many forms of literature including fairy tales. One of the famous fairy tales is Frau Holle, a fairy tale originating from Germany and collected by the Grimm Brothers in their collection entitled Children's and Household Tales (Kinder- und Hausmärchen). The formulation of the problem in this study is how is the oppression of women in the fairy tale Frau Holle? The purpose of this research is to analyze how the oppression of women in Frau Holle's fairy tales. The research method in this study is a qualitative method with content analysis techniques. There is oppression of women in this fairy tale which is done by differentiating women based on gender stereotypes, injustice in treatment, coercion and violence, and rewards and punishments. Based on the results of the analysis of Frau Holle's fairy tale, there are elements of oppression against women by teaching that women must follow certain rules to be appreciated, while those who do not obey the rules will be punished.Keywords: Feminism, Frau Holle’s Tale, Women’s Oppression